Client-server Architecture, a Review - Geofrey Nyabuto (International Journal of Advanced Science and Computer Applications, 2024)
Client-server architecture is a software model through which resources and requests are serviced over a network. The client requests a resource over a network, and the server receives the request, processes it, and responds appropriately. With this model, multiple users can simultaneously access and use resources. This paper provides an overview of the architecture, outlining its characteristics, advantages, disadvantages, different implementations of the architecture as well as the current and future of this architecture.